Decade-long effects of integrated farming systems on soil aggregation and carbon dynamics in sub-tropical Eastern Indo-Gangetic plains - Rao, Karnena Koteswara; Samal, Saubhagya Kumar; Kumar, Sanjeev; Singh, Nongmaithem Raju; Kumar, Rakesh; Mondal, Surajit; Kumar, Santosh; Mishra, Janki Sharan; Bhatt, Bhagwati Prasad; Ravisankar, N.; Kumar, Sunil; Upadhyay, Pravin Kumar; et al. (Frontiers in Sustainable Food Systems, 2024)
Integrated farming system (IFS) aims to diversify the agricultural landscapes by incorporating different components to meet the multifarious needs of burgeoning population. Present study was undertaken to understand the impact of different cropping systems on soil organic carbon (SOC) stock, aggregate distribution, and aggregate associated organic carbon (AAOC) in 2-IFS models of varying sizes (0.4 and 0.8 ha) established during 2008-09. After 10 years of the study, fodder system registered the greatest TOC and carbon stocks across IFS models, with surface soil (0-15 cm) accumulating 17 and 13% higher TOC and C stock, respectively in 0.4 and 0.8 ha models. In 0-15 cm, macroaggregates (Ma) represented the highest proportion (75-76%) in both the models.Among cropping systems, fodder system recorded the highest large macroaggregates in both IFS model. Within 0-30 cm depth, small macroaggregates mostly found in perennial system (fodder, guava+turmeric and lemon intercropping system) indicating potential to improve the aggregate stability over seasonal (shorter duration) system. In general, micro aggregate (Mi) fraction was pre-dominant in sub surface soil (17.35%). The maximum AAOC was found in Ma than with Mi fractions; with about 67 and 63% of total carbon associated with Ma in 0.4 and 0.8 ha IFS models, respectively. Interestingly, 0.8 ha IFS model had higher TOC ( 11 %) and carbon stock ( 12 %) than 0.4 ha model, but AAOC did not show similar result indicating the influence of cropping systems on AAOC. The study indicated that fodder-based production system had a better performance in terms of soil physical health in terms of increasing aggregate stability and content of soil carbon. This is indicative of advantages of perennial-based system over seasonal or annual-based cropping systems for soil sustainability in Eastern Indo-Gangetic Plains.